Lightweight Approach Of Xml Implementation As Industrial Standard For Information Sharing - Erwin Widodo (Jurnal Teknik Industri, 2007)
Information sharing in supply chain has emerged as one critical factor in maintaining company's responssiveness. This ability is needed to overcome both the supplier and customer requirements in sharing their data to accomplish their operational routines. A lot of efforts have been devoted in such research area including XML (eXtensible Markup Language) technology. However, a stepwise approach on how to utilize this advance technology is still lacking. This paper proposed a lightweight approach to implement XML in information sharing firmly. The main XML characteristics will be exploited so that the advantages of utilizing this mark up language may be highlighted. Based on these important remarks a lightweight approach of implementing XML is possible to be composed. The expected outcome is a step-by-step guidance for data exchanger to utilize XML simply but precisely and accurately. A case study of information sharing in commerce is elaborated to enhance our understanding on how to implement this approach in real domain problem.